Corpus evidence for lexical and genre effects in the metaphorical conceptualization of negative self-evaluative emotions: The case of shame and embarrassment - Karolina Krawczak (Language and Cognition)
Do different emotion terms trigger different metaphorical conceptualizations of emotions? What are the effects of the discourse context of the genre on metaphor choice in the conceptualization of emotion concepts? Finally, are such lexical and discourse–contextual effects on emotion-targeted metaphor choice quantifiable? Prior discourse-oriented research has demonstrated from a largely qualitative perspective that metaphor use is dynamic and sensitive to discursive contextual variables (e.g., Deignan et al., 2013; Semino 2010, 2011; Semino et al., 2013; Dorst 2015; Caballero 2016; Knapton & Rundblad, 2018). In the present study, these questions are addressed from a corpus-based multivariate perspective, where detailed qualitative analysis of found examples is combined with quantitative modeling. The study examines negative self-evaluative emotions in English, operationalized through their two nominal exponents, i.e., shame and embarrassment, as attested in the discourse context of three genres – fiction, magazine and spoken TV language. The data are first analyzed qualitatively for relevant contextual variables and then modelled quantitatively. The results demonstrate that while both lexical and genre effects are observed in metaphor choice in the conceptualization of negative self-evaluative emotional experience, their combined effect should also be accounted for, as these two variables are found to interact with each other.